DIGITAL IMAGE ENHANCEMENT USING THE METHOD OF MULTISCALE RETINEX AND MEDIAN FILTER - Mhd Furqan; Abdul Halim Hasugian; Rizqi Hidayat Tanjung (INFOKUM, 2020)
At this time digital image used by a lot of people to capture the moment or other important things, digital image itself is the result of shooting with a digital camera, although today's digital cameras are already equipped with features that support the results of the picture, but not all digital image that is produced in accordance with our wishes, it happens because of a problem on the quality of the image, situation and condition at the time of the shooting process the image will affect on the quality of the image causes the image results to be bright or dark. Then from that needed improvement of the quality of the image so that the image that is produced in accordance with our wishes, in this study, the methods used in improving the quality of image is using the method of Multiscale Retinex and Median Filters. The process of Multiscale Retinex will produce the image of a more bright compared to the original image that minimal light intensity, while the Median filter will produce a clearer image because it can reduce the noise/noise in the image, the parameters used in this study is Histogram of some data that has been researched histogram chart shows the value of the intensity of the pixel average is close to zero (0) after processed by the method of Multiscale Retinex and the Median Fiter value of the intensity of the pixel average show a change of the charts is approaching 250 which indicates an increase in the brightness of the digital image brighter.